INCREASING WATER PRODUCTIVITY OF LOWLAND RICE THROUGH THE WATER SAVING TECHNIQUES AND CROP MANAGEMENT IN RESPONSE TO DROUGHT - Didiek Setiobudi; Hasil Sembiring (Agromet, 2009)
The water saving technology for lowland rice cultivation was very crucial because of in the future irrigation water become scarce and competed with other sectors. The lowering of the availability of irrigation water had the impact for sustainability of rice production. The review of the paper described the pattern of basic water requirement, yield responses of several lowland rice varieties to moisture stress, days interval irrigation and the alternatives of water saving techniques for improving yield and water productivity. The pattern of the actual water requirement (ET+P&S) showed the maximum value of 8.8 mm/day (1.02 lt/sec/ha) for high yielding varieties (HYV) that occurred from heading to 50% flowering. Under limited water supply, irrigation water should be applied that period to prevent yield loss. Soil moisture stress at moderate level (- 0.5 bar) from heading to full flowering was significantly decreased yield about 30% when compared with the yield of continuously flooded 3 cm depth. This period was a critical period of HYV to soil moisture stress. For rotational irrigation purposes, information of the optimum days interval irrigation was important. It was found that 3 days irrigation interval was a critical limit for HYV to achieve higher yield. The SRI model of rice cultivation had the lowest rice yield in the lowland soil, poor drainage, clay soil texture and low permeability. The modified irrigation of the SRI plus fertilizer N based on LCC readings gave a greater yield as well as water productivity. The hybrid and NPT line rice varieties had higher yield components and grain yield than Ciherang variety. Ciherang variety was not favor to grown for the wet season, it was more productive when grown in dry season even with AWD irrigation model. The plant spacing of 25 cm x 25 cm gave higher number of panicle/hill and number of spikelet/panicle under both AWD and continuously flooded 3 cm depth for dry and wet season consistently. The fertilizer N management based on SSNM with low and high rates for the early vegetative stage were not significantly affected all yield components and grain yield. The AWD irrigation could save irrigation water about 18% when compared to the continuously flooded conditions.The grain yield of the hybrid, inbred and NPT line rice varieties was higher for the dry season than wet season under both AWD irrigation and continuous flooding consistently.